JENIS KEPEMILIKAN DALAM SISTEM EKONOMI ISLAM - MEIRISON MEIRISON (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The theme of the article is "economy based on the principles of Islam". In the matter of ownership, individuals, society and the State as the subject of the economy have its own property rights, established by the sharia. The concept of ownership becomes very clear presented by Taqiyuddin an-Nabhani in his book Islamic economic system. In this book explained that Islam divides the concept of ownership becomes: individual ownership (private property); public ownership; and possession of the State (private state). Individual ownership is an individual right recognized by the sharia which such rights a person may have a wealth of moving or not moving. This right is protected and restricted by sharia law and no control. Moreover someone can finally have the authority to manage the assets held. Public ownership is all the wealth that has been set ownership by Allah to the Muslims so that the wealth of the Muslims belongs together. Individuals are allowed to take advantage of the wealth, but forbidden to have it personally. Islam recognizes the right of private property (individual) and allows businesses and individual initiative in using and managing personal wealth. Islam also has certain limitations in accordance shariah so that a person can use his private property without harming the public interest. However, there are some common interests that can not be managed and owned by individuals, but all of it belongs to and managed by the State for public interest.